Neonates colonized with pathogenic bacteria in the airways have a low‐grade systemic inflammation. Issue 11 (11th October 2018) - Rahman Fink, N.; Chawes, B. L.; Thorsen, J.; Stokholm, J.; Krogfelt, K. A.; Schjørring, S.; Kragh, M.; Bønnelykke, K.; Brix, S.; Bisgaard, H.
Abstract: Background and objectives: The development of childhood asthma is associated with neonatal colonization with pathogenic bacteria in hypopharynx. Furthermore, established asthma is associated with systemic low‐grade inflammation. We here report on the association between neonatal colonization with pathogenic bacteria in hypopharynx and the development of systemic low‐grade inflammation. Methods: Bacterial colonization of the hypopharynx with Moraxella catharralis, Haemophilus influenzae, and/or Streptococcus pneumoniae was assessed in asymptomatic children from the Copenhagen Prospective Studies on Asthma in Childhood2000 (COPSAC2000 ) cohort at age 1 month by culturing technique (N = 238) and by quantitative polymerase chain reaction (qPCR) technique (N = 249) and in the COPSAC2010 cohort by culturing at age 1 month (N = 622) and again at age 3 months (N = 613). Systemic low‐grade inflammation was determined in both cohorts at age 6 months by measuring plasma levels of high‐sensitivity C‐reactive protein (hs‐CRP), tumor necrosis factor‐α (TNF‐α), and interleukin‐6 (lL‐6). Results: In both cohorts, bacterial colonization was associated with increased levels of hs‐CRP: COPSAC2000, 1 month culturing (geometric mean ratio of colonized/noncolonized [95% CI]), 1.39 [0.97‐2.01], P = .08; 1 month qPCR, 1.55 [1.14‐2.10], P < .01; COPSAC2010, 1 month, 1.52 [1.23‐1.87], P < .01; and 3 month, 1.57 [1.30‐1.90], P < .01. A multiparametric principal component analysis incorporating hs‐CRP, TNF‐α, and IL‐6 confirmed a systemic inflammatory profile in children colonized with M. catharralis, H. influenzae . and/or S. pneumoniae in the hypopharynx compared to noncolonized children ( P ‐values < .05). Conclusion: The composition of the upper airway microbiome in early life may cause systemic low‐grade inflammation. Abstract : Airway bacterial colonization was determined in nasopharyngeal samples of children age 1 month in the COPSAC2000 (n = 238) and COPSAC2010 (n = 613) cohorts. Systemic low‐grade inflammation was determined by measurement of high sensitivity CRP, IL‐6 and TNF‐α in blood samples from the children age 6 months. Early life development of systemic low‐grade inflammation may be influenced by neonatal airway bacterial colonization.